Heritage of repressions – assignment to state - Čekutis, Ričardas (Genocidas ir rezistencija, 2004)
On 22–24 October 2003 Vilnius University hosted a unique international scientific conference Psychology of Severe Trauma: Long–Term Implications of Political Repression. The conference was organised by the Genocide and Resistance Research Centre of Lithuania (in Lithuanian – LGGRTC) in cooperation with psychologists from Vilnius University, and was attended by researchers from Germany, Norway, Canada, and Latvia. Until now, not only in our country, but also in the whole of Eastern Europe, no attempt has been made for an in–depth analysis into the long–term psychological trauma suffered because of political repression.
Keywords: Soviet occupation; repressions; political prisoners; deportees; psychological trauma